Resolution of prison riots : strategies and policies - Useem, Bert (OUP E-Books., 1996)
The book uses eight diverse case studies of prison riots to explore how the outcomes were affected by policies, procedures, management, communications, and strategy immediately before, during, and after the riot. Exploring the results achieved by negotiation, by force, and by simply waiting, the authors illuminate the factors most important in controlling the costs of damage and human suffering that can result from increasingly common prison disturbances.